The evolution of CCS-EOR technology diffusion involving multi-agent participation under dual carbon targets: A system dynamics and prospect theory approach - Zhang, Weiwei; Chen, Ximei; Wang, Yunxiang; Zhu, Kanglin; He, Lan (Sustainable futures, 2025)
Reconciling economic advancement with carbon reduction and energy efficiency has become imperative for climate-resilient sustainable development. Carbon Capture and Storage with enhanced oil recovery (CCS-EOR) as the pivotal way of CO2 utilization, it is of great significance to explore how to promote the widespread diffusion of CCS-EOR through multi-agent collaboration mechanisms. In pursuit of sustainable economic and environmental development, this study develops an evolutionary game model integrating prospect theory and system dynamics to examine the interactive relationships among the government, coal-fired power plants (CFPPs), and oilfield enterprises within the technology chain. Prospect theory is employed to establish payment and benefit matrices for the participating subjects, while system dynamic identifies crucial parameters. Finally, numerical simulation is conducted to explore the system equilibrium state of the tripartite evolutionary game. The results indicate that: (1) Augmenting the subsidy for clean electricity generation can enhance the investment probability of CFPPs while diminishing government investment, whereas increasing CO2 utilization subsidies can boost investment probability of oil enterprises but reduce government investments. (2) To effectively facilitate the diffusion of CCS-EOR technology, the carbon penalty factor should be kept above 0.7, while the carbon price should remain below 160 CNY/ton. Otherwise, it will diminished the cooperation probability between CFPPs and oil enterprises. (3) The government’s initial investment subsidy factor should be maintained at 0.2–0.3, while the clean electricity subsidy and CO2 utilization subsidy factor are suggested to be 0.35–0.55 CNY/kWh and 0.2–0.4, respectively. The findings provide theoretical underpinnings and policy recommendations to promote CCS-EOR technology diffusion.